1996
DOI: 10.1159/000267895
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Aqueous-Flare Reaction to Repeated Applications of Prostaglandin E2to the Cornea in Pigmented Rabbits

Abstract: To evaluate the effect of single or repeated topical applications of prostaglandin E2 (PGE2) to the cornea on the blood-aqueous barrier, we have measured the extent of flare in the anterior chamber of rabbit eyes at various time intervals. PGE2 was applied to the cornea for 4 min with the use of a glass cylinder in pigmented rabbits. Aqueous flare was measured by a laser flare cell meter. The flare intensity following the second application of 25 or 50 μg/ml of PGE2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…Aqueous flare elevation, mean B standard deviation, following transcorneal PGE 2 using a glass cylinder in the present study was similar to that observed in our previous study [2]. In the present study, isopropyl unoprostone induced aqueous flare elevation in the rabbit eye.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Aqueous flare elevation, mean B standard deviation, following transcorneal PGE 2 using a glass cylinder in the present study was similar to that observed in our previous study [2]. In the present study, isopropyl unoprostone induced aqueous flare elevation in the rabbit eye.…”
Section: Discussionsupporting
confidence: 91%
“…Studies from our laboratory previously reported that transcorneal diffusion of prostaglandin E 2 (PGE 2 ) using a glass cylinder induced aqueous flare elevation in pigmented rabbits, and that the elevation was reproducible when PGE 2 was applied at an interval of more than 1 week [1,2]. We also reported that topical instillation of betaxolol, an antiglaucoma agent, inhibited PGE 2 -induced aqueous flare elevation in pigmented rabbits [3].…”
mentioning
confidence: 99%
“…We also reported that intravenous nicardipine, 2 mg/kg body weight, inhibited the acute rise of aqueous flare and intraocular pressure induced by argon laser photocoagulation in pigmented rabbits [3]. We further showed that when 50 Ìg/ml of PGE 2 was applied every day for 6 days, the flare intensity decreased significantly day by day [4]. In the present study, we examined whether or not a small dose of nicardipine or nilvadipine (another calcium channel blocker) inhibits these effects induced by PGE 2 , and also investigated whether or not a daily administration of nilvadipine shows the effect.…”
Section: Introductionmentioning
confidence: 74%
“…The aqueous flare elevation was decreased following the repeated applications of PGE 2 within a short time (hourly or daily). However, weekly applications of PGE 2 did not change the aqueous flare reaction in pigmented rabbits [4]. In the present study, therefore, the eyes received 2 applications of PGE 2 or EP agonist at an interval of 1 or 2 weeks.…”
Section: Discussionmentioning
confidence: 57%
“…Studies from our laboratory have previously reported that two applications of prostaglandin E 2 (PGE 2 ) reproducibly induced aqueous flare elevation in the same eye at 1-week intervals [3,4] and that intravenous injection of certain calcium channel blockers (nilvadipine and nicardipine) inhibited the experimental elevation of aqueous flare in pigmented rabbits [5,6]. We further studied the effect of highly selective agonists for prostaglandin E 2 receptor subtypes (EP1, EP2, EP3 and EP4) on the blood-aqueous barrier in pigmented rabbits and found that ONO-AE1-259-01 (EP2 agonist) and ONO-AE1-392 (EP4 agonist) induced aqueous flare elevation, while ONO-DI-004 (EP1 agonist) and ONO-AE-248 (EP3 agonist) had almost no effect [7].…”
Section: Introductionmentioning
confidence: 99%